Podstawowy warsztat patrystyczny homilisty - Wasilewski, Edward (Studia Pastoralne, 2016)
The opinions provided by the Magisterium of the Church clearly emphasize the prescriptive and fundamental value of the teaching of the Church Fathers. A homilist who seeks exemplary solutions should not only resort to the treasure trove of the Fathers’ doctrine, but also adapt his teaching to their didactic and group-related model. The homilist’s techniques should be organized so as to facilitate direct access to the relevant passages of the Church Fathers. A key to it is subject-related indices in handbooks or in source publications of the the Fathers’ works.